THE DEVELOPMENT OF STOCK ENDOWMENTS AS ONE OF THE PHILANTHROPIES FOR MUSLIM INVESTORS - Nadia Ulfa (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2023)
Since the inauguration of the stock waqf by the Indonesia Stock Exchange in 2019 and along with the large number of sharia investors reaching 117,942 investors in 2022, it has considerable potential in stock endowments. The purpose of this study is to determine the development of stock endowments for Muslim investors. Using qualitative research methods using normative juridical approaches, collection techniques: primary data comes from literature studies and secondary data comes from distributing questionnaires to stock investors. The results of this discussion can be concluded that the existence of stock waqf is a description of money waqf that has been practiced by the public before the MUI fatwa in 2002 concerning money endowments, then stock endowments were officially launched by IDX in 2019. Based on the questionnaire distributed to investors, investors more dominantly answered that they already knew the stock endowments, then the existence of Law No. 41 of 2004 had been recognized but the distribution was more dominant assuming it was not distributed properly. And there is only 1 person who has ever endowd shares.